2011
DOI: 10.1111/j.1472-8206.2011.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of the serotonergic, noradrenergic, and dopaminergic systems in the antidepressant‐like action of riparin III obtained from Aniba riparia (Nees) Mez (Lauraceae) in mice

Abstract: Previous work has shown that intraperitoneal administration of riparin III (ripIII) reduces immobility time in the forced swimming test (FST), which suggests potential antidepressant activity. As the mechanism of action is not completely understood, this study is aimed at investigating the antidepressant-like action of ripIII. Following intraperitoneal administration of ripIII at doses of 25 and 50 mg/kg, there were decreases in the immobility time in the FST and tail suspension test without accompanying chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
3
10
0
2
Order By: Relevance
“…These findings are in agreement with data from the scientific literature, which support the anxiolytic and antidepressant actions of Riparin III in basic studies (Melo, 2012;Sousa et al, 2004). A previous study, using models of acute depression, verified normalization of depressive behavior and an additional increase in monoamine levels (Melo et al, 2013). The same study concluded that Riparin III was able to increase the levels of monoamines NA, 5-HT, and DA in the striatum and prefrontal cortex, and NA and 5-HT in the hippocampus, while decreasing their metabolites in the striatum and prefrontal cortex (Melo et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings are in agreement with data from the scientific literature, which support the anxiolytic and antidepressant actions of Riparin III in basic studies (Melo, 2012;Sousa et al, 2004). A previous study, using models of acute depression, verified normalization of depressive behavior and an additional increase in monoamine levels (Melo et al, 2013). The same study concluded that Riparin III was able to increase the levels of monoamines NA, 5-HT, and DA in the striatum and prefrontal cortex, and NA and 5-HT in the hippocampus, while decreasing their metabolites in the striatum and prefrontal cortex (Melo et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…A previous study, using models of acute depression, verified normalization of depressive behavior and an additional increase in monoamine levels (Melo et al, 2013). The same study concluded that Riparin III was able to increase the levels of monoamines NA, 5-HT, and DA in the striatum and prefrontal cortex, and NA and 5-HT in the hippocampus, while decreasing their metabolites in the striatum and prefrontal cortex (Melo et al, 2013). Riparin III can probably be used as an anti-depressant and anxiolytic in women during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of specific antagonists, it was observed that Rip III showed antidepressant effects in the forced swimming test. These effects seem to be related to the modulation of the alpha 1 and alpha 2 noradrenergic systems, the serotonergic system, and the D2 dopaminergic system [21,22]. No changes were detected in the open field test [21,22].…”
mentioning
confidence: 91%
“…In this sense, recent studies conducted by our group provided evidence for the involvement of the serotonergic, noradrenergic and dopaminergic systems in the antidepressant-like action of rip II [6] and rip III [13]. In this sense, recent studies conducted by our group provided evidence for the involvement of the serotonergic, noradrenergic and dopaminergic systems in the antidepressant-like action of rip II [6] and rip III [13].…”
Section: Introductionmentioning
confidence: 67%